Reproductive Outcomes of In Vitro Fertilization and Fresh Embryo Transfer in Infertile Women With Adenomyosis: A Retrospective Cohort Study - Liang, Tingting; Zhang, Wen; Pan, Ningning; Han, Bing; Li, Rong; Ma, Caihong (Frontiers in Endocrinology, 2022)
Background: Adenomyosis is commonly encountered in infertile women; however, it is still unclear whether adenomyosis has a detrimental effect on in vitro fertilization and embryo transfer (IVF-ET) outcomes. Method: We enrolled 1146 patients with adenomyosis and 1146 frequency-matched control women in a 1:1 ratio based on age, BMI, and basal follicle-stimulating hormone (FSH) level. After controlling for other factors, the rates of clinical pregnancy, miscarriage, live birth, and obstetric complications were compared between the two groups. Results: There was no significant difference in clinical pregnancy rate between the two groups (38.1% vs. 41.6%; P=0.088). The implantation rate (25.6% versus 28.6%, P=0.027) and live birth rate (26% versus 31.5%, P=0.004) were significantly lower in the women with adenomyosis than in the controls. The miscarriage rate in the adenomyosis group was higher than that in the control group (29.1% versus 17.2%, P=0.001). In terms of obstetric complications, the severe preterm birth rate (7.72% versus 1.66%, P<0.001) and neonatal low birth weight (21.9% vs. 10.8%, P<0.001) were significantly higher in the women with adenomyosis than in the controls, and the incidence of placenta previa and preeclampsia were significantly higher in the adenomyosis group than in the control group (4% vs. 1.4% and 6% vs. 2.8%, respectively, P=0.033, P=0.038). Conclusion: Adenomyosis has a negative effect on IVF-ET outcomes in that the miscarriage risk is increased, the live birth rate is reduced, and the severe preterm birth rate and obstetric complications are increased.